The SEP-SEQ Trial: Clinical Validation of the Karius Plasma Next-Generation Sequencing Test for Pathogen Detection in Sepsis. (4th October 2017) - Thair, Simone; Seng, Hon; Hollemon, Desiree; Hong, David; Blauwkamp, Timothy; Kertesz, Mickey; Ho, Carine; Mann, Rosen; Quinn, James; Yang, Samuel
Abstract: Background: Sepsis is a leading cause of death and can be caused by a wide range of potential pathogens. In up to 40% of cases, a causative pathogen is never identified. There is a need for improved diagnostic tests that can accurately identify the breadth of potential pathogens to inform effective antimicrobial therapy. Methods: We enrolled a prospective cohort of patients presenting to the hospital with signs and symptoms of sepsis. Plasma samples were collected for NGS testing at time of initial blood culture. Extracted plasma cell-free DNA was sequenced, human sequences removed and remaining reads aligned against a pathogen database consisting of viruses, bacteria, and eukaryotic pathogens. Relative abundance was estimated; pathogens present at high statistical significance were identified. NGS results were compared with a composite reference standard of all microbiology testing performed within 7 days of admission and clinical diagnosis. Results: Of 286 patients enrolled, plasma NGS identified potential pathogens in 60.1% (172 of 286) of septic subjects including DNA viruses, bacteria (including fastidious/unculturable bacteria like Mycobacterium tuberculosis ), and fungi. In contrast, 15.7% (45 of 286) subjects had a positive initial blood culture and 38.1% (109 of 286) had a potential infectious etiology identified using a composite microbiology laboratory standard. The NGS plasma assay had a positive agreement of 86.7% (39 of 45) and 79.5% (78 of 98) compared with initial blood culture (after excluding contaminants) and the composite laboratory reference standard, respectively. After clinical adjudication, 81.4% (140 of 172) of the positive plasma NGS results were deemed to be consistent with the septic event. Of the remaining 32 subjects, 15 had NGS results that were plausible causes of sepsis but clinical were insufficient to confirm this. Conclusions: With a single blood draw, the Karius plasma NGS assay identified a broad range of pathogens in septic patients three times more often than blood culture and more often than all microbiology tests combined. This plasma NGS test can identify a viruses, bacteria, and eukaryotic pathogens which can provide valuable information to help clinicians better target antimicrobial therapy for patients with sepsis. Disclosures: H. Seng, Karius, Inc.: Employee, Salary. D. Hollemon, Karius, Inc.: Employee, Salary. D. Hong, Karius, Inc.: Employee, Salary. T. Blauwkamp, Karius, Inc.: Employee, Salary. M. Kertesz, Karius, Inc.: Employee, Salary. S. Yang, Karius, Inc.: Research Contractor, Research grant.